A bioinspired molybdenum–copper molecular catalyst for CO2 electroreduction. Issue 21 (18th May 2020) - Mouchfiq, Ahmed; Todorova, Tanya K.; Dey, Subal; Fontecave, Marc; Mougel, Victor
Abstract : A bimetallic Mo–Cu complex inspired by the active site of the carbon monoxide dehydrogenase enzyme mediates the electroreduction of carbon dioxide to formic acid. Abstract : Non-noble metal molecular catalysts mediating the electrocatalytic reduction of carbon dioxide are still scarce. This work reports the electrochemical reduction of CO2 to formate catalyzed by the bimetallic complex [(bdt)Mo VI (O)S2 Cu I CN] 2− (bdt = benzenedithiolate), a mimic of the active site of the Mo–Cu carbon monoxide dehydrogenase enzyme (CODH2). Infrared spectroelectrochemical (IR-SEC) studies coupled with density functional theory (DFT) computations revealed that the complex is only a pre-catalyst, the active catalyst being generated upon reduction in the presence of CO2 . We found that the two-electron reduction of [(bdt)Mo VI (O)S2 Cu I CN] 2− triggers the transfer of the oxo moiety to CO2 forming CO3 2− and the complex [(bdt)Mo IV S2 Cu I CN] 2− and that a further one-electron reduction is needed to generate the active catalyst. Its protonation yields a reactive Mo V H hydride intermediate which reacts with CO2 to produce formate. These findings are particularly relevant to the design of catalysts from metal oxo precursors.